The impact of China's foreign trade on their Actual-Open Emissions of CO2 in the years 2000-2020 in the context of EU energy policy - Bartosz Fortuński (The Central European Review of Economics and Management (CEREM), 2024)
Aim: This article aims to analyze the impact of China's trade with 78 major trading partners on Actual-Open Emission of CO2 (EAO) from 2000 to 2020 in light of the European Union's (EU) goal to reduce CO2 emissions by 20% by 2020 compared to 1990 levels. Research Methods: The research is based on the Actual-Open Emission of CO2 model and employs the circular flow model to assess the influence of China's foreign trade on CO2 emissions during the years 2000-2020. Findings: The study revealed that China's foreign trade significantly influenced its CO2 emissions in all years analyzed, with positive contributions to EAO due to a trade surplus (exports exceeding imports). As the world's largest exporter and the second-largest importer, China's trade activity resulted in substantial CO2 emissions. Four key indicators were identified as influencing the difference between Official-Close Emission of CO2 (EOC) and EAO: China's GDP, the percentage of exported GDP, the percentage of imported GDP, and EOC levels. These findings highlight the significant role of trade in China's CO2 emissions, which is critical in the context of EU initiatives like "Fit for 55.
Keywords: F18; Q54; Q56; 330; International trade; China; CO2 emissions; EU energy policy